Pengaruh Kompensasi dan Motivasi Kerja terhadap Kinerja Karyawan dengan Kepuasan Kerja sebagai Variabel Mediasi pada Organisasi Oppio Coffe Yogyakarta - Ilvan Arjun Angody; Prayekti Prayekti (Reslaj : Religion Education Social Laa Roiba Journal, 2023)
The purpose of this study is to describe (1) the effect of compensation on employee performance. (2) The effect of work motivation on employee performance. (3) the effect of job satisfaction on employee performance. (4) job satisfaction mediates the effect of motivation on employee performance. (5) job satisfaction mediates the effect of compensation on employee performance. This research is a type of quantitative research, with a population of all employees of Oppio Coffee Yogyakarta. The sampling technique in this study is a non-probability sampling technique where the technique used is saturated sampling (census). The number of samples in this study were 53 employees of Oppio Coffee Yogyakarta. Data collection techniques in this study using a questionnaire. The data analysis methods used in this research are validity test, reliability test, descriptive test, classical assumption test, multiple linear regression and Sobel test. Data analysis was conducted to identify the independent variables that affect the dependent variable.The results showed that (1) compensation had no positive and significant effect on employee performance. (2) Compensation has no positive and significant effect on employee job satisfaction. (3) Job satisfaction has a positive and significant effect on employee performance. (4) job satisfaction as a mediating variable of the effect of compensation on employee performance has a positive and significant effect. (5) Job satisfaction as a mediating variable the effect of work motivation on employee performance has a positive and significant effect. Keywords : compensation, work motivation, employee performance, job satisfaction.